Correlation of DNA load, genotyping, and clinical phenotype of Mycoplasma pneumoniae infection in children - Wang, Wei; Wang, Lu; Yin, Zhaoqing; Zeng, Shujuan; Yao, Guohua; Liu, Yuqiao; Fang, Yulian; Ma, Cuian; Cui, Hualei (Frontiers in Pediatrics, 2024)
Introduction: This study aimed to investigate the correlation between Mycoplasma pneumoniae (MP)-DNA load in the bronchoalveolar lavage fluid (BALF) of children with MP pneumonia (MPP) and its subtypes, relevant laboratory data, imaging, extrapulmonary complications in infected children, and its clinical significance in evaluating the disease. Methods: Children hospitalized with MPP at Tianjin Children's Hospital were selected, excluding those with mixed viral, bacterial, and fungal infections. Children were divided into low- and high-load groups according to the MP DNA load in BALF using real-time quantitative fluorescence polymerase chain reaction (PCR). After a successful MP culture, positive specimens were subjected to PCR-Restriction fragment length polymorphism and Multiple-locus variable number tandem repeat analysis typing. Basic data, clinical information, laboratory data, and radiological results were collected from all children included in the study. Results: The PI-I type dominated the different load groups. Children in the low-load group had more wheezing and shortness of breath; however, children in the high-load group had a higher length of hospitalization, maximum fever temperature, higher chills/chilliness, incidence of abdominal pain, and higher C-reactive protein (CRP), procalcitonin (PCT) and aspartate aminotransferase (AST) levels. Children in the high-load group were more likely to have imaging changes such as pleural effusion, and the incidence of respiratory infections and extrapulmonary complications was higher than that of those in the low-load group. We applied Spearman’s correlation analysis to clarify the relationship between MP DNA load and the clinical severity of MPP. We found that MP DNA load was positively correlated with length of hospitalization, maximum fever temperature, CRP, PCT, Interleukin-6 (IL-6), and AST levels, and negatively correlated with fever and cough durations, white blood cell count (WBC), and proportion of monocytes (MONO). The degree of correlation was as follows: length of hospitalization > IL-6 > cough duration > AST > fever duration > PCT > WBC > proportion of MONO > maximum fever temperature > CRP levels. Conclusions: MP DNA load was not correlated with MP typing but was significantly correlated with the children’s clinical phenotype. Therefore, the MP DNA load helps in the early diagnosis of infection and can better predict disease regression.